Modern Ideas about Dysfunction of the Meibomian Glands - I. B. Medvedev; V. N. Trubilin; E. G. Poluninа; N. N. Dergacheva; D. V. Andzhelova; Yu. V. Evstigneeva; K. V. Chinenova (Oftalʹmologiâ)
Purpose: to develop a comprehensive method of meibomian gland dysfunction (MGD) treatment, including the periorbital zone massage, aimed to improving the microcirculation of the eyelids and the functional activity of the meibomian glands, evaluating its effectiveness and safety.Patients and methods. The study included 92 patients (184 eyes) with all forms of permanent residence in accordance with the international classification of the DEWS working group, 32 of them were men and 60 women. All patients included in the study at the first stage of work were randomly divided into 3 groups, depending on the type of therapy. The first group included 34 patients (68 eye), in which complex therapy was carried out in the form of eyelid hygiene + massage in the periorbital zone according to the methodology developed during the study, the second group included 30 patients (60 eyes) who underwent IPL therapy (the use of intense pulsed light in the periorbital zone), the third group included 28 patients (56 eyes) who were treated in the form of eyelid hygiene (warm compresses + eyelid self-massage).Results and discussion. A technique of massage in the periorbital zone was developed, its effect on hemodynamic parameters of the eyelids was studied, and to assess its effectiveness, a comparison of hemodynamic parameters of the eyelids was carried out with two other methods of thermal exposure — eyelid hygiene (warm compresses + eyelid self-massage) and IPL therapy. It was found that all three types of exposure — IPL therapy, eyelid hygiene and eyelid hygiene + massage in the periorbital zone, carried out according to the original technique, lead to an increase in hemodynamic parameters of the eyelids and in the lacrimal artery (according to laser Doppler flowmetry and color Doppler mapping) to varying degrees of severity, which should contribute to an increase in the metabolism of Meibomian glands, therefore, and the improvement of their functional activity. At the same time, 3 months after the treatment starting, the improvement of the the meibomian glands’ functional activity of was higher in the group of patients in which IPL therapy and complex effects — eyelid hygiene + massage in the periorbital zone were performed, compared with the group with only eyelid hygiene. However, after 6 months, high indicators of the functional activity of the meibomian glands remained only in the group with complex effects — eyelid hygiene + massage in the periorbital zone. Such a therapeutic effect, according to the results of the study, improves the patients’ quality of life according to data of the SPEED questionnaire and directly depends on adherence to treatment on the Morisky scale (MMAS).Conclusions. The presented complex of therapy can be recommended for wide application in ophthalmological practice for the treatment of dysfunction of the meibomian glands.